Collaborative Education Empowerment in Indonesia - Lela, Kamila Wahdah Noor; Mubtadik, Mohamad Ayyub; Marlina, Yuli; Lestary, Veronika Nugraheni Sri; Nurdianto, Heri (Bisma : Bimbingan Swadaya Masyarakat, 2023)
This study explores the concept of Collaborative Education Empowerment in Indonesia, focusing on the active involvement of local communities in the design and implementation of educational strategies. The research employs Participatory Action Research (PAR) to engage teachers, students, local authorities, and community members in identifying educational challenges and co-designing solutions. Key findings indicate that community-based learning initiatives, inclusive education practices, and peer-learning models significantly enhance student engagement, teacher effectiveness, and community cohesion. However, challenges such as limited resources, teacher training, and resistance to change were identified as barriers to sustaining these efforts. The study emphasizes the role of social capital, including trust and cooperation, in facilitating these educational reforms. Policy recommendations are made to ensure the sustainability of these initiatives, including increased government support for teacher development and inclusive practices. The research contributes to the understanding of how collaborative education can address educational disparities and promote more equitable learning environments in Indonesia